The Dynamics of Therapeutic Relationships in Cybercounseling in Modern Guidance and Counseling Services - Nurul Faqih; Melisa Wulandari; Mutiara Putri; Widia Widia; Muhammad Fadillah Prayogie (Sustainable, 2024)
The development of digital technology has driven the transformation of guidance and counseling services through the implementation of cyber counseling. This service offers flexibility, efficiency, and expanded access for clients, but also presents complex dynamics in the form of challenges, obstacles, and opportunities. Cyber ​​counseling, as an innovation in guidance and counseling (BK) services in the digital era, presents a significant transformation in the therapeutic relationship between counselors and clients. This article aims to analyze the dynamics of the therapeutic relationship in cyber counseling by examining the challenges, obstacles, and opportunities that arise in the cultural, ethical, technical, and digital literacy contexts. The research used a desk study method by analyzing various literature related to digital counseling. The results of the study indicate that therapeutic relationships in virtual spaces face cultural challenges, data security risks, limitations in nonverbal communication, infrastructure barriers, and counselor competency readiness. However, cyber counseling also opens up significant opportunities for expanding service access, improving digital literacy, and innovating counseling intervention methods. With strengthened regulations, increased digital competence, and institutional support, cyber counseling has the potential to become a modern BK service model that is effective, ethical, and adaptive to current developments.